Efficiency of Agro Commodity Futures Market - Singh, Narinder Pal (Prabandhan: Indian Journal of Management, 2010)
India is an agricultural country and one third of its population still depends on the sector directly or indirectly. With a share of about 20% in the national GDP as compared with the level of 50% in 1947, agriculture continues to the mainstay of the Indian economy. Agriculture sector is an important factor in achieving a GDP growth of 8-10%. All this indicate that India can be promoted as a major centre for trading of commodity derivatives.Commodity derivatives are contracts which do not have value of their own but derive their value from the underlying commodity like wheat, rice, sugar, oil, gold, silver etc. Commodity derivatives have a crucial role to play in price risk management process especially in any agriculture denominated economy. Instability of commodity prices has always been a major concern of the producers as well as the consumers in agriculture denominated country like India. Farmers' direct exposure to price fluctuations, for instance, makes it too risky for many farmers to invest in otherwise profitable activities. Commodity derivatives market is a place where these farmers and traders can reduce their price risk. These contracts enable them to lock in the prices of the products well in advance. Moreover, futures prices give necessary indicators to producers and consumers about the likely future ready (spot) price and demand and supply conditions traded.